Influence of genetic susceptibility on the urinary excretion of 8-hydroxydeoxyguanosine of firefighters. Issue 6 (1st June 2000) - Hong, Yun-Chul; Park, Hye-Sook; Ha, Eun-Hee
Abstract : OBJECTIVES: Oxidative DNA damage has been implicated in carcinogenesis. The DNA damage can be assessed from the urinary excretion of the DNA-repair product 8-hydroxydeoxyguanosine (8-OH-dG). The factors were investigated that influenced the excretion of urinary 8-OH-dG in 78 firefighters. METHODS: 53 Out of 78 firefighters were exposed to fire within 5 days of the study and 25 were not. 8-OH-dG was measured by ELISA and the distribution of the genotypes of CYP1A1, CYP2E1, GSTM1, and GSTT1 was measured by polymerase chain reaction. RESULTS: The homozygous wild type frequencies of CYP1A1 Msp I, CYP1A1 ile-val, CYP2E1, GSTM1, and GSTT1 were 31.5%, 56.2%, 60.3%, 50.7%, and 53.4%, respectively. The geometric mean of urinary 8-OH-dG was 14.1 ng/mg creatinine in more active firefighters and 12.3 ng/mg creatinine in non-exposed and less active subjects. Significantly increased concentrations of urinary 8-OH-dG were found to be associated with cigarette smoking, and 14% of the variation of 8-OH-dG was explained by cigarettes smoked per day. The CYP1A1 Msp I, CYP1A1 ile-val, GSTM1, and GSTT1 genetic polymorphisms were not found to be significantly associated with the urinary excretion of 8-OH-dG. However, the subjects carrying the CYP2E1 mutant type excreted higher concentrations of 8-OH-dG and there was a marginally significant interaction of GSTT1 with firefighting activity. Multiple regression analysis confirmed that smoking was the strongest predictor of excretion of 8-OH-dG. Age, body mass index, and firefighting activity were not significant predictive factors for urinary 8-OH-dG. CONCLUSION: Smoking and CYP2E1 gene polymorphism may be important factors in carcinogenesis and the GSTT1 positive genotype may be a genetic susceptibility factor in firefighters who are exposed regularly to various chemical carcinogens.